Menopause, Sindroma Metabolik dan Terapi Hormon: Menopause, Metabolic Syndrome and Hormone Therapy - susilo, Jatmiko; Indah Kurniawati; Dedi Haswan; Al Hajar Fuadatus Zurroh; Neli Diah Pratiwi (Universitas Ngudi waluyo, 2025)
Estrogens play a crucial role in protecting against insulin resistance (IR) by regulating metabolic processes that govern energy balance and mitigating inflammation. In postmenopausal women, the decline in estrogen levels significantly increases the risk of developing insulin resistance. This decline leads to impaired insulin action and secretion, paving the way for persistent hyperglycemia, hyperlipidemia, hypertension, and obesity—key components of metabolic syndrome (MetS). These factors not only elevate the risk of cardiometabolic disorders but also substantially increase the likelihood of developing Type 2 Diabetes Mellitus (T2DM) and cardiovascular disease (CVD). The protective benefits of estrogen against insulin resistance are critical, especially as these benefits diminish with menopause. However, they can be restored through hormone replacement therapy, presenting an effective strategy for mitigating these health risks. This review underscores the vital protective role of estrogen regarding insulin resistance as part of metabolic syndrome and emphasizes the importance of hormone therapy in developing proactive preventive strategies. To build on this understanding, a comprehensive search was conducted across PubMed, using MeSH terms like “Metabolic Syndrome,” “Estrogen,” “Menopause,” “Insulin Resistance,” “Type 2 Diabetes Mellitus,” “Cardiovascular,” “Dyslipidemia,” and “Hormone Therapy.” Out of 200 articles, 168 were identified as relevant to the topic, focusing on studies published between 2015 and 2025, ultimately narrowing down to 102 significant articles. This extensive research lays the groundwork for enhancing preventive measures in women’s health. Abstrak Estrogen dapat melindungi dari perkembangan resistensi insulin (IR) dengan memodulasi proses metabolisme yang terlibat dalam keseimbangan energi dan menurunkan regulasi dan/atau menekan peradangan. Kadar estrogen yang berkurang pada wanita pascamenopause meningkatkan resiko IR. Gangguan kerja insulin dan/atau sekresi insulin berkontribusi terhadap perkembangan dan keberlanjutan hiperglikemia, hiperlipidemia, hipertensi, dan obesitas, yang merupakan ciri khas sindroma metabolik (MetS), dengan konsekuensi utama berkembangnya gangguan kardiometabolik, berupa peningkatan resiko yang signifikan terhadap perkembangan diabetes mellitus tipe 2 (DMT2) dan/atau penyakit kardiovaskuler (PKV). Perlindungan terhadap IR ini didorong oleh hormon estrogen, yang cenderung menghilang dengan timbulnya menopause tetapi dapat dibangun kembali dengan terapi penggantian hormon. Tinjauan ini mengevaluasi pengetahuan terkini tentang peran protektif estrogen terkait dengan IR yang merupakan komponen dari suatu kondisi yang dikenal sebagai MetS dan kaitannya dengan terapi hormon untuk mendorong pengembangan strategi pencegahan yang lebih efektif. Sebanyak 200 artikel PubMed dipilih menggunakan istilah MeSH seperti: “Sindrom Metabolik”, “Estrogen”, “Menopause”, “Resistensi Insulin”, “Diabetes Melitus tipe 2”, “Kardiovaskuler”. “Dislipidemia” dan “Terapi Hormon”. Seleksi relevansi dengan topik 168 artikel, seleksi tahun terbit (2015 – 2025) terpilih 102 artikel